KONSEP KESALEHAN SOSIAL JAMAAH MAIYAH SIMPUL JAMPARING ASIH BANDUNG - Husnul Qodim (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2021)
A lucky human is someone who can be useful to the other people. Allah SWT gives peacefulness to them who concern to social needs. This study, using qualitative methods or research that processes data in the form of the words of the author or oral of the object being observed. While the data source comes from the official Maiyah website and the Maiyah Simpul Jamparing Asih congregation in Bandung. Furthermore, the data collection technique uses in-depth interviews, participant observation, literature study and documentation. As well as the population of this study amounted to 25 people, while the sample in this study were 9 followers of Maiyah Simpul Jamparing Asih. And the analysis technique is descriptive method. The results of this study indicates that the followers of Maiyah Simpul Jamparing Asih are educated deeply about the importance of helping others. Meanwhile, the benefits of following simpul jamparing asing are mental strength, magnitude of heart, obsessed to help others, and also avoid to judge or respect someone because of their wealth and position